If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23x + 17y = 11 Solving 23x + 17y = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17y' to each side of the equation. 23x + 17y + -17y = 11 + -17y Combine like terms: 17y + -17y = 0 23x + 0 = 11 + -17y 23x = 11 + -17y Divide each side by '23'. x = 0.4782608696 + -0.7391304348y Simplifying x = 0.4782608696 + -0.7391304348y
| 9x+12+13y-10=180 | | 8k-3+8k=4K-3 | | X-1=3x-8+5x | | 2x-40=2y | | (4x^4y^9/z^8)^2 | | d^3-12d^2+36d=0 | | 5(30)+12=0 | | B+5=-9+7x | | 3/4-3/4x=1/8 | | -4+5v=-19 | | log(x)=-2.8831916 | | (1/2x)-7/4=-8/3 | | x^2+14x=23 | | 6(x-2)-3x=15 | | 21=6+3u | | 49z=1 | | -6x+9=7 | | t^4-3t^3-40t=0 | | 10(13v)=-8(6v+1) | | 5x+12=7x-34 | | 66=2L+2(20) | | -12=y/5-2 | | 2w+7(w+3)=3 | | -4/5=(-4/3u)-1/2 | | 12n-9=-1+4n | | 7.25x-x=9.375 | | -2w+7(w+3)=3 | | f(10)=X-7 | | 8+2(2x-4)-x=9-3(-3x+1)-11x | | 0.18g/3.0ml | | 4(5m-3)=8 | | x-5.5=-3.4 |